AfricaConnect3: Connecting Africa to Unlimited possibilities - Dekkar, Leila; Fiore, Silvia (AfricaConnect3, 2021)
Despite the availability of infrastructures having significantly progressed over the recent years, tertiary education and research institutions in Africa are still among the least connected in the academic world, a situation that is particularly critical for landlocked countries. In this context, the AfricaConnect3 project strives to establish secure, adequate, and affordable network infrastructures and offers dedicated services to African National Research and Education Networks (NRENs), as well as builds adequate human resource capacities and expertise within the community and raises the awareness of the role of digital transformation for research and education (R&E). This paper aims to present the achievements and impact of AfricaConnect3 on African R&E communities, as well as advocating for NRENs, by detailing the activities implemented and services offered to R&E institutions in Africa. Finally, this paper addresses the need for NRENs to be better represented in the African digital landscape and understood as part of the solution.
Keywords: National Research and Education Network; Higher Education; Digitalization